The Social Influence of Brand Community: Evidence from European Car Clubs - Algesheimer, René; Dholakia, Utpal M.; Herrmann, Andreas (Journal of Marketing, 2005)
The authors develop and estimate a conceptual model of how different aspects of customers’ relationships with the brand community influence their intentions and behaviors. The authors describe how identification with the brand community leads to positive consequences, such as greater community engagement, and negative consequences, such as normative community pressure and (ultimately) reactance. They examine the moderating effects of customers’ brand knowledge and the brand community's size and test their hypotheses by estimating a structural equation model with survey data from a sample of European car club members.